Is Laminar Cartilage Composition as Determined by T2 Relaxometry Associated with Incident and Worsening of Cartilage or Bone Marrow Abnormalities?. (December 2021) - Roemer, Frank W.; Eckstein, Felix; Duda, Georg; Guermazi, Ali; Maschek, Susanne; Sharma, Leena; Wirth, Wolfgang
Objective: To test the hypothesis that superficial cartilage composition (T2) is associated with subsequent incidence or worsening of cartilage damage, and deep T2 with that of bone marrow lesions (BMLs) in knees without radiographic osteoarthritis (ROA). Design: A total of 201 knees from the Osteoarthritis Initiative without ROA were included: 78 from the healthy reference cohort, 60 without ROA but with risk factors, and 63 without ROA but with contralateral ROA. Year 1 (Y1) superficial and deep cartilage T2 were derived in the medial and lateral (weightbearing) femur (MF/LF) and tibia (MT/LT), using sagittal multiecho spin echo magnetic resonance images. Cartilage and BMLs were assessed in the medial (MFTJ) and lateral femorotibial joint (LFTJ) at Y1 and 3 years later. Binary logistic regression statistics were applied. Results: Incidence or worsening of cartilage damage was more frequent (MFTJ 15%, LFTJ 13%) than incidence or worsening of BMLs (6.0%, 4.5%). In knees with incident or worsening cartilage lesions in the MF and LT, deep layer T2 in the same plate was elevated (MF, 43.6 ± 4.0 vs. 41.3 ± 3.8 ms, P = 0.047; LT, 33.8 ± 2.3 vs. 32.0 ± 2.2 ms, P = 0.008) compared to those without. In knees with incident or worsening of BMLs in the LFTC and LT, superficial layer T2 was elevated (LFTJ, 49.6 ± 4.8 vs. 46.7 ± 3.1 ms; LT, 47.4 ± 4.9 vs. 44.0 ± 3.3 ms, both P s = 0.04). Conclusions: Contrary to our hypothesis, increased deep layer cartilage T2 was associated with subsequent worsening of cartilage damage, whereas superficial layer T2 was related to subsequent BML worsening. Yet, this relationship was observed in some, but not in all cartilage plates.